2011
DOI: 10.1074/jbc.m111.256909
|View full text |Cite
|
Sign up to set email alerts
|

Helix 8 Plays a Crucial Role in Bradykinin B2 Receptor Trafficking and Signaling

Abstract: Upon activation the human bradykinin B 2 receptor (B 2 R) acts as guanine nucleotide exchange factor for the G proteins G q/11 and G i . Thereafter, it gets phosphorylated by G protein-coupled receptor kinases (GRKs) and recruits ␤-arrestins, which block further G protein activation and promote B 2 R internalization via clathrin-coated pits. As for most G protein-coupled receptors of family A, an intracellular helix 8 after transmembrane domain 7 is also predicted for the B 2 R. We show here that disruption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 48 publications
1
41
0
Order By: Relevance
“…Interestingly the crystal structure of the MOR revealed the potential of a tight interaction between TM5 and TM6 of the MOR, a region highly conserved between MOR and DOR. In several instances, H8, a region that has been known to be important for receptor signal transduction (Tetsuka et al, 2004;Feierler et al, 2011), is involved in the dimer interface (Salom et al, 2006;Manglik et al, 2012;Wu et al, 2012). In our experiments, it appears that H8 needs to remain intact for functional complementation to occur, which would be in line with those previous findings.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly the crystal structure of the MOR revealed the potential of a tight interaction between TM5 and TM6 of the MOR, a region highly conserved between MOR and DOR. In several instances, H8, a region that has been known to be important for receptor signal transduction (Tetsuka et al, 2004;Feierler et al, 2011), is involved in the dimer interface (Salom et al, 2006;Manglik et al, 2012;Wu et al, 2012). In our experiments, it appears that H8 needs to remain intact for functional complementation to occur, which would be in line with those previous findings.…”
Section: Discussionsupporting
confidence: 83%
“…Our studies demonstrated that the helical state of the helix 8 region is responsible for binding to the cytoplasmic protein FNT ( Figure 4); furthermore, residues on the hydrophobic side of the helix 8 region are completely conserved among the two FNT-binding receptors CCR2 and CCR5 ( Figure 5). Previous reports have demonstrated important roles for the helix 8 region in receptor activation [26][27][28], although the molecular mechanisms remain unclear. The results of the present study provide new insight into the regulation mechanism mediated by helix 8, in which the hydrophobic side of helix 8 serves as a binding site for a cytoplasmic regulator.…”
Section: Discussionmentioning
confidence: 98%
“…It is not known if this Cys 516 is actually modified in vivo. A potential eighth helix at the C terminus (Asn431-Gln451) is suggested by sequence similarities to bradykinin R2 and other receptors (Feierler et al, 2011). Interestingly, the C5a 1 and C5a 2 receptors do not have this basic sequence and also contain proline, a potential helix blocker.…”
Section: A Introductionmentioning
confidence: 99%